A Pengembangan Bahan Ajar Berbentuk Majalah Elektonik Untuk Materi Kunci Determinasi dan Kladogram Kelas X Melalui Studi Etnobotani dan Fitokimia - Yetty Hastiana; Rusdy A. Siroj; Irma Irma (BIOEDUSCIENCE, 2021)
Background: The use of teaching materials in learning can improve learning results. It requires interesting teaching materials whose material is in accordance with the basic competencies to be achieved. One of the teaching materials that can be used is an electronic magazine. The purpose of this study was to determine the validity, practicality, and potential effects of the use of teaching materials on study results. In the key material of determination and cladogram. Methods: Development research was carried out using the 4D model, with the research subjects of class X students at SMAN 2 Palembang. Result: (1) the validity was 100% from a material expert, 89% from linguists, 75% from media experts; (2) practically is known that the NRS is 91% of students and 98% of biology teachers; (3) the N-gain test obtained a score of 0,64 with the medium potential category to improve learning outcomes in the realm of knowledge, while for the skills of students, they were able to make and present cladogram. Conclusion: Teaching materials in the form of electronic magazines are declared valid, practical, and have sufficient potential to improve study results. Suggestions: (1) this teaching material is suitable for use in school where the majority of students have the availability of facilities, such as gadgets, quota, and conducive learning environment; (2) it is hoped that other researchers will use this teaching material to see the consistency of potential effects of teaching material on learning results.